On the Issue of Etiology of Macrophage Granuloma in Respiratory Organs and Lymph Nodes: Cases from Practice - V. A. Cinserling; V. E. Karev; A. O. Avetisyan; M. D. Chernyh; M. S. Tlostanova (Журнал инфектологии)
.